2010
DOI: 10.1016/j.appdev.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of deficits in emotional clarity to stress responses and depression

Abstract: This research investigated the contribution of deficits in emotional clarity to children’s socioemotional adjustment. Specifically, this study examined the proposal that deficits in emotional clarity are associated with maladaptive interpersonal stress responses, and that maladaptive interpersonal stress responses act as a mechanism linking deficits in emotional clarity to childhood depressive symptoms. Participants included 345 3rd graders (M age = 8.89, SD = .34) assessed at two waves, approximately one year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
108
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 61 publications
10
108
1
Order By: Relevance
“…Higher scores on this measure indicate greater levels of emotional clarity. Flynn and Rudolph (2010) demonstrated that the ECQ has good internal consistency and convergent validity through significant correlations with congruent behavioral measures that assess emotional processing abilities, such as identifying affect through facial expressions. The ECQ also demonstrated adequate internal consistency for the current sample (Time 1, α = .81; Time 3, α = .88).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores on this measure indicate greater levels of emotional clarity. Flynn and Rudolph (2010) demonstrated that the ECQ has good internal consistency and convergent validity through significant correlations with congruent behavioral measures that assess emotional processing abilities, such as identifying affect through facial expressions. The ECQ also demonstrated adequate internal consistency for the current sample (Time 1, α = .81; Time 3, α = .88).…”
Section: Methodsmentioning
confidence: 99%
“…High emotional clarity is associated with conscientiousness, active coping strategies, positive reinterpretation of stressful events, and increases in well-being among adults (Gohm & Clore, 2002). Emotional clarity is hypothesized to be adaptive because the ability to discriminate among and comprehend one’s own emotions allows for resources to be allocated towards goal-directed behaviors and cognitions rather than towards recognizing one’s own emotional experiences (Flynn & Rudolph, 2010; Gohm & Clore, 2000). …”
mentioning
confidence: 99%
“…Both RA and internalizing problems have a substantial interpersonal component (Flynn & Rudolph, 2010;Xie, Swift, Cairns, & Cairns, 2002), and some studies suggest that both are more common among females than males (Brown, Arnold, Dobbs, & Doctoroff, 2007;Crick & Grotpeter, 1995;Murray-Close et al, 2007). Theory suggests that RA and internalizing problems may be reciprocally related, causing a worsening cycling effect across time.…”
Section: The Association Between Ra and Internalizing Problemsmentioning
confidence: 96%
“…Indeed, the ability to control impulsive behaviours and engage in goal directed behaviours when distressed, as well as the ability to acknowledge, accept, monitor, and evaluate negative and positive Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/psychres emotions in a manner that highlights both of these affective states as functional, may be important in maintaining healthy emotional equilibrium. This is plausible, given that deficits in these latter response tendencies have been implicated in reduced resilience for coping with stress, heightened vulnerability to depressive symptoms, neuroticism, rumination and anxiety disorders, all of which are associated with BD (Salovey et al, 1995;Gohm and Clore, 2002;Tull and Roemer, 2007;Flynn and Rudolph, 2010).…”
Section: Introductionmentioning
confidence: 96%